ARCHAISM IN MANDAILINGESE - Syahron Lubis; Namsyah Hot Hasibuan (Fakultas Sastra Universitas Negeri Malang, 2015)
The aim of the present study is to investigate and record archaic words and expressions in Mandailingese, an ethnic language spoken in the regency of Mandailing-Natal, North Sumatra. The design of this study is qualitative-descriptivein which the data were collected by interviewing eight native speaker informants and by examining some old written texts of Mandailingese culture. The result of the studyshows that there are approximately 350 archaic words and expressions found and recorded. They are categorized into noun, verb, adjective, and adverb.